Nurse Jackie. Season four [videorecording (DVD)] - Falco, Edie; Best, Eve, 1971-; Facinelli, Peter, 1973-; Wever, Merritt; Schulze, Paul; Fumusa, Dominic, 1969-; Smith, Anna Deavere; Cannavale, Bobby (Lionsgate, 2013)
Jackie Peyton, a strong-willed and brilliant but very flawed emergency room nurse. This season, Jackie comes to realize that both karma and sobriety can be a pain. In addition to finally confronting her addiction, Jackie's street smarts and sardonic wit are tested even further by an ambitious new hospital administrator determined to run a tight ship and keep Jackie in line.